Comparative (Within Species) Genomics of the Vitis vinifera L. Terpene Synthase Family to Explore the Impact of Genotypic Variation Using Phased Diploid Genomes - Smit, Samuel Jacobus; Vivier, Melané Alethea; Young, Philip Richard (Frontiers in Genetics, 2020)
The Vitis vinifera L. terpene synthase (VviTPS) family was comprehensively annotated on the phased diploid genomes of three closely related cultivars: Cabernet Sauvignon, Carménère and Chardonnay. VviTPS gene regions were grouped to chromosomes, with the haplotig assemblies used to identify allelic variants. Functional predictions of the VviTPS subfamilies were performed using enzyme active site phylogenies resulting in the putative identification of the initial substrate and cyclisation mechanism of VviTPS enzymes. Subsequent groupings into conserved catalytic mechanisms was coupled with an analysis of cultivar-specific gene duplications, resulting in the identification of conserved and unique VviTPS clusters. These findings are presented as a collection of interactive networks where any VviTPS of interest can be queried through BLAST, allowing for a rapid identification of VviTPS-subfamily, enzyme mechanism and degree of connectivity (i.e. extent of duplication). The comparative genomic analyses presented expands our understanding of the VviTPS family and provides numerous new gene models from three diploid genomes.